The Economic Impact of Religious Tourism in Indonesia: A Systematic Literature Review (SLR) - Febrianti, Kayyisah Fathin; Handoko, Luqman Hakim (Jurnal Magister Ekonomi Syariah, 2025)
This study aimed to analyze the current state of the literature on the role of religious tourism in economic growth in Indonesia. The research employed the Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) protocol. This study also used VOSviewer for keywords analysis. A total of 129 articles were systematically screened, resulting in 19 relevant studies. The findings indicate that religious tourism significantly contributes to income generation, job creation, MSME development, and local government revenue. However, these economic benefits are not evenly distributed across all regions and are influenced by factors such as destination management, community involvement, and government support. Literature trends reveal growing academic interest, yet publications are predominantly from non-indexed journals and focused mainly on Java. In addition based on keywords analysis, identifies five thematic clusters that highlight key research directions in religious tourism, emphasizing its socio-economic impacts, cultural significance, and potential contributions to community welfare and regional development.